An observer’s measure of de Sitter entropy - Mehrdad Mirbabayi (Journal of High Energy Physics)
Abstract The two-point correlation function of a massive field ⟨χ(τ)χ(0)⟩, measured along an observer’s worldline in de Sitter (dS), decays exponentially as τ → ∞. Meanwhile, every dS observer is surrounded by a horizon and the holographic interpretation of the horizon entropy S dS suggests that the correlation function should stop decaying, and start behaving erratically at late times. We find evidence for this expectation in Jackiw-Teitelboim gravity by finding a topologically nontrivial saddle, which is suppressed by e − S dS $$ {e}^{-S_{dS}} $$ , and which gives a constant contribution to | ⟨χ(τ)χ(0)⟩ |2. This constant might have the interpretation of the late-time average of | ⟨χ(τ)χ(0)⟩ |2 over all microscopic theories that have the same low-energy effective description.